STRATEGIES FOR ENGAGING STUDENTS THROUGH COMMUNICATION (Лучшие интеллектуальные исследования, 2025)
Abstract:This article explores effective strategies for engaging students in the learning process through communication. It highlights the importance of active participation, constructive feedback, and the use of relatable examples to foster interest and understanding. The article also emphasizes the role of technology in enhancing communication, such as digital platforms, multimedia tools, and interactive activities. Additionally, it discusses the value of creating a supportive environment, using humor and empathy, and encouraging peer collaboration to build trust and motivation.